Epidural hematoma in the pediatric population - case study = Krwiak nadtwardówkowy w populacji pediatrycznej - opis przypadku - Kamila Woźniak; Dorota Małgorzata Ratuszek-Sadowska; Maciej Śniegocki (Kazimierz Wielki University, 2015)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. Epidural hematoma in the pediatric population - case study = Krwiak nadtwardówkowy w populacji pediatrycznej - opis przypadku. Journal of Education, Health and Sport. 2015;5(8):243-252. ISSN 2391-8306. DOI 10.5281/zenodo.28216 http://dx.doi.org/10.5281/zenodo.28216 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A243-252 https://pbn.nauka.gov.pl/works/608458 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-67a48fe5-300f-4ef4-b02c-ba2f9b605908 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015.   Krwiak nadtwardówkowy w populacji pediatrycznej - opis przypadku   Epidural hematoma in the pediatric population - case study   Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1   • 1.          Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland   • 2.          Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 2.Chair and Department of Rehabilitation Medicine, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland     Streszczenie Urazy głowy są głównymi przyczynami zgonu i nabytych zaburzeń neurologicznych. Odmienny niż u dorosłych przebieg urazu głowy w populacji dziecięcej powoduje, że w tej grupie zdarza się najwięcej nieoczekiwanych powikłań. Z uwagi na brak specyficznych objawów klinicznych krwiak nadtwardówkowy w populacji pediatrycznej stanowi duże wyzwanie zarówno diagnostyczne jak i lecznicze. Autorzy przedstawiają opis przypadku i postępowania u 6- letniego dziecka po urazie głowy,  z rozpoznanym w badaniu obrazowym krwiakiem nadtwardówkowym.   Słowa kluczowe: uraz czaszkowo-mózgowy, krwiak nadtwardówkowy, populacja pediatryczna.   Abstract Head injuries are the main causes of death and acquired neurological disorders. Differently than adults mileage head injury in the pediatric population means that in this group it happens most unexpected complications. Given the lack of specific clinical symptoms epidural hematoma in the pediatric population is a major challenge for both diagnostic and therapeutic. The authors present a case and proceedings in a child 6 years old after a head injury diagnosed in the study imaging epidural hematoma.   Key words: cephalo-cerebral trauma, epidural hematoma, pediatric population.